Bringing the Sun to the Fields: : Reflections from Egypt’s Shift to Solar Farming - Rashid, Siti Norzaemah Binti Mohd; Aminludin, Nur Azemah Binti (BIODIVERS - BIOTROP Science Magazine, 2025)
In response to the growing challenges of diesel powered irrigation, Egypt’s El Beheira Governorate has embraced solar-powered systems to support more sustainable agricultural practices. This article reflects on Egypt’s transition, focusing on the environmental, economic, and social impacts of solar irrigation. With notable improvements in water efficiency, reduced pollution, and better rural livelihoods, this case study highlights solar energy’s potential as a catalyst for greener farming.